Using Cultural Capital for Urban Management, Khon Kaen Municipality, Thailand - Vilachai, Kanta (European Journal of Sustainable Development, 2017)
Creative economy development is an invaluable way to develop Thailand economy, moreover, the cultural capital development is also the important tool to develop creative economy. This qualitative research aimed to evaluate the cultural capital application in the members of KhonKaen municipal council and others for the urban management. The data were collected by using the participatory observation and in-depth interview. The results show that 1) “Isan wooden buddha statues”, a cultural capital in Isan region, have been used as “tool” of urban management which encouraged by members of KhonKaen municipal council and 2) KhonKaen municipality applied “Isan wooden buddha statues” as a “tool” and “issue” in KhonKaen urban management affairs. In conclusion, this provides an opportunity for promote people participation to conduct a new kind of related to creative the sustainable urban developmentor put the cultural content as a part of the social bonds strategies. Keywords: Urban Management/ Cultural Capital Management/ Sustainable Development